CLASS - CHANGING DERIVATIONAL SUFFIXES IN CHILDREN’S STORY BOOK ENTITLED “MAGNIFICENT MILLIE” - Retno Budi Astuti; Erna Pranata Putri (Universitas Gunadarma, 2026)
Mastering knowledge of a language entails understanding its lexicon. Morpheme is one of the numerous basic units in morphology. Derivational suffixes are found in bound morphemes. Derivational suffixes can change the category and kind of meaning of the form to which they apply, resulting in the creation of a new word. This article examines the class-changing derivational suffixes in a children’s story book entitled “Magnificent Millie”. This research used descriptive-qualitative method to discover and understand how language, specifically suffixation, is utilized to construct meaning in a text. The research data is collected by using a documentation technique. The research object is a children’s story book entitled “Magnificent Millie”. The result of this study shows that class-changing derivational suffixes can be found in a children’s story book entitled “Magnificent Millie”. the researcher found 15 data of class-changing derivational suffixes which is divided into 10 data of noun derivation, 4 data of adverb derivation, and 1 datum of adjective derivation. This shows that children’s story book can be a good medium to learn about derivational suffixes.